Uniquely and arbitrarily shaped laser resonators using 2D InAsP/InP photonic crystals. Issue 25 (1st December 2013) - Lu, T.‐J.; Kim, S.‐H.; Postigo, P.A.; Regreny, P.; Seassal, C.; Scherer, A.
Abstract : Uniquely and arbitrarily shaped photonic crystal laser cavities were designed, fabricated and characterised. Room temperature lasing emitting at about 1550 nm was observed for all devices when photopumped by an 830 nm wavelength pulse laser with a pulse width of 100 ns. Continuous‐wave lasing was even observed for select devices.